L'argumentation dans Le Mythe de Sisyphe d'Albert Camus - Beji, Jihene (2022)
The purpose of this article is to describe and analyze the argumentative path adopted by Albert Camus in Le Mythe de Sisyphe, more precisely in a chapter indicated below with the same title. The analysis is intended to be linguistic and to follow the pragmatic perspective. Some questions will be raised, mostly relating to the argumentative approach (illustrated by the means implemented, the aim of the argumentator, the expected perlocutionary effect) and a final question will relate to the effectiveness or ineffectiveness of the argumentative enterprise of the author.